Analisis Problematika Pembentukan Lingkungan Bahasa Arab : (Studi Kasus Di Prodi PBA STAI Ali Bin Abi Thalib Surabaya) - Dagi Mardhan Agae Agni; Hermawan Hermawan (STAI Ali bin Abi Thalib Surabaya, 2025)
This study aims to analyze the problems in establishing the Arabic language environment in the Arabic Language Education (PBA) Study Program at STAI Ali bin Abi Thalib Surabaya. The focus of the research covers three main aspects: (1) the actual condition of the Arabic language environment on campus, (2) the supporting and inhibiting factors in its establishment, and (3) the strategies implemented to improve the effectiveness of building such an environment. The research employs a qualitative approach with a case study design. Data collection techniques include in-depth interviews, participatory observation, and documentation involving students as well as the language and dormitory management staff. The data were analyzed using Miles & Huberman’s interactive analysis technique, which consists of data reduction, data display, and conclusion drawing/verification. The findings reveal that although there is institutional commitment to fostering an Arabic language environment, its implementation in practice remains partial and has not been fully internalized within the campus’s academic culture. Language activities tend to be confined to formal settings and do not yet reflect natural interaction in students’ daily lives. Inhibiting factors include weak monitoring of language policy enforcement, low internal motivation among students, inconsistency in program implementation, and an ineffective reward-and-punishment system. The strategies applied so far are largely administrative, such as drafting regulations and issuing formal instructions, but they have not sufficiently addressed the affective and motivational aspects of students. The study highlights that building an Arabic language environment requires a more comprehensive approach, not only addressing obstacles but also optimizing existing supporting factors. Habituation-based approaches, motivation reinforcement, and the integration of formal and informal elements are essential for creating a sustainable language environment. Therefore, this study recommends collaborative strategies among all academic community members to strengthen the language culture on campus.